![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x^3-2x^2+3x-6=x\left(x^2+3\right)-2\left(x^2+3\right)=\left(x-2\right)\left(x^2+3\right)\)
b, \(x^2+2x+1-4y^2=\left(x+1\right)^2-\left(2y\right)^2=\left(x+1-2y\right)\left(x+1+2y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(x-2y=3\Rightarrow\hept{\begin{cases}x=3+2y\\y=\frac{x-3}{2}\end{cases}}\)
\(\Rightarrow A=2x\left(x+2y-3\right)-y\left(6x-3y-10\right)+x-7+\left(x-3y\right)^2\)
\(=2x^2+4xy-6x-6xy+3y^2+10y+x-7+x^2-6xy+9y^2\)
\(=3x^2+12y^2-8xy-5x+10y-7\)
\(=3.\left(3+2y\right)^2+12y^2-8\left(3+2y\right).y-5\left(3+2y\right)+10y-7\)
\(=3\left(9+12y+4y^2\right)+12y^2-8\left(3y+2y^2\right)-15-10y+10y-7\)
\(=27+36y+12y^2+12y^2-24y-16y^2-15-10y+10y-7\)
\(=8y^2+12y+5\)
\(M=\left(x^2-2x+1\right)\left(1+2x\right)-\left(x^2+2x+1\right)\left(1-3x\right)-\left(3-6x\right)\left(x^2+3x+2\right)\)
\(=x^2+2x^3-2x-4x^2+1+2x-x^2+3x^8-2x+6x^2-1+3x-3x^2-9x-6+6x^8\)\(+18x^2+12x=11x^3+17x^2+4x-6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\)
\(\Rightarrow2A=8.\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\)
\(=\left(3-1\right)\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\)
\(=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\)
.....
\(=\left(3^{64}-1\right)\left(3^{64}+1\right)\)
\(=3^{128}-1\)
\(\Rightarrow A=\frac{3^{128}-1}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(M=\left(a+b\right)\left(a^2-ab+b^2\right)+3ab\left[\left(a+b\right)^2-2ab\right]+6a^2b^2\left(a+b\right)\)
\(=\left(a+b\right)\left[\left(a+b\right)^2-3ab\right]+3ab\left[\left(a+b\right)^2-2ab\right]+6a^2b^2\left(a+b\right)\)
\(=1-ab+3ab\left(1-2ab\right)+6a^2b^2\)
\(=1-3ab+3ab-6a^2b^2+6a^2b^2=1\)
Vậy M=1
M = a3 + b3 + 3ab( a2 + b2 ) + 6a2b2( a + b )
= ( a + b )3 - 3ab( a + b ) + 3ab[ ( a + b )2 - 2ab ] + 6a2b2( a + b )
= 13 - 3ab.1 + 3ab( 12 - 2ab ) + 6a2b2.1
= 1 - 3ab + 3ab - 6a2b2 + 6a2b2
= 1
\(A=\left(3+1\right)\left(3^2+1\right)...\left(3^{64}+1\right)\)
\(\Leftrightarrow\left(3-1\right)A=\left(3-1\right)\left(3+1\right)\left(3^2+1\right)...\left(3^{64}+1\right)\)
\(\Leftrightarrow2A=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\)
\(\Leftrightarrow2A=\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)...\left(3^{64}+1\right)\)
\(\Leftrightarrow2A=3^{128}-1\)
\(\Leftrightarrow A=\frac{3^{128}-1}{2}\)